History of diagnosis on idiopathic inflammatory myopathy - Wei ZHANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2016)
The idiopathic inflammatory myopathy (IIM) is a group of clinically heterogeneous, autoimmune-mediated disorders characterized by inflammation of muscle, elevated creatine kinase (CK), interstitial lung disease and other organ systems involvement. Dermatomyositis (DM), polymyositis (PM) and inclusion body myositis (IBM) are three major subtypes of IIM. "Necrotic myopathy" is firstly described as a pathological concept and later considered as an independent disease entity. Necrotizing autoimmune myopathy (NAM) is a newly recognized subtype of IIM since the year of 2004. NAM tends to show a distinct disease profile in clinical presentation, immune markers, muscle imaging as well as muscle pathology which have not been fully described. Therefore in this article, we will review the advances in the classification and diagnosis of IIM and focus on the characteristics of NAM.   DOI: 10.3969/j.issn.1672-6731.2016.10.002